Pengaruh Sport Massage Terhadap Kebugaran Pemain Women Futsal Universitas Muhammadiyah Palopo - Bangon, Ririn Romba; Riswanto, A. Heri; Saman, Saman (Jurnal Porkes, 2025)
This study aims to determine the effect of sport massage. This research data was collected through pretest and posttest. The population used in this study was the entire women's futsal team of Muhammadiyah University of Palopo which amounted to 15 people. The sampling technique is saturated sample. The data used is quantitative data. That the pretest value gets a minimum average value of 23.2 and a maximum average value of 30.6 with a mean value of 26.00, with a standard deviation of 2.2517 while that the posttest value gets a minimum average value of 29.5 and a maximum average value of 40.2 with a mean value of 32.813 with a standard deviation of 3.0636. The results of the classical assumption test with Shapiro-Wilk can be seen that this data is normally distributed because the posttest value (085) > 0.05, so the data is normally distributed, then the results of the homogeneity test can be seen that sig. based on mean is 310. Because the value of 310 > 0.05, it can be concluded that the data variance is homogeneous, the results of the hypothesis test can be seen that this data shows that the students' pretest and posttest scores are significant. The static test shows Asymp.Sig (2tailed) t value (001 < 0.05), it can be said that sport massage has a significant effect on the fitness of women futsal players.